Children solve problems - De Bono, Edward (Allen Lane Penjuin Education : Allen Lane Penjuin Education, 1972)
Children solve problems effortlessly. Their ideas may often be impractical, but they produce them with a fluency, a zest and an irrepressible imagination which ought to be the envy of many an adult, and especially those who are paid to solve difficult problems. Nevertheless, it is primarily as a fascinating insight into the processes of the mind that Edward de Bono offers this very rich collection of children's thinking. The nine tasks the children were set included a machine to weigh elephants, a system for building a house quickly, a sleep machine, a space rocket, improvements to the human body, and methods of helping the police deal with bad men. Each task was carefully chosen to involve the children in coping with problems of a distinct character, and Edward de Bono's introductions and commentaries point out many insights into the childhood imagination and world view.
Keywords: Problem solving in children; Problem Solving; Psychology, Child